Quizizz-Based Learning Innovation to Improve the Achievement of Islamic Religious Education - Anggraini, Fadhilla Nangroe; Mustofa, Triono Ali (Universitas Muhammadiyah Surakarta, 2024)
Educational innovation is a new and rapid advance in the world of education. Especially in the era of globalization that is rife with technology. The growing use of technology also affects the development of education, which trends with the use of technology. Through educational innovation, the quizizz application is an online platform to develop learning through interactive quiz games to make learning more interesting. This study aims to describe how the implementation of quizizz-based learning has improved islamic educational achievement and to determine the supporting and inhibiting factors in the implementation of quizizz-based learning innovation in improving islamic religious education achievement. The research is qualitative, with a case study approach where researchers examine an existing case. Data collection techniques use observation, interviews, and documentation. Observation by directly observing the object that is the place of research and interviews essentially obtain direct information in fact from the resource person, namely islamic education teachers. The results of the study show that the implementation of the application of the quizizz can be used as an assessment in arabic and muhammadiyahan subjects. The use of quizizz is nothing but a secondary learning method or as a support in learning, not as a primary method in teaching. The success of the quizizz application can be seen in the increase in student learning motivation, student activeness in class, and other student learning achievements. The supporting factor for applying quizizz is that students are increasingly open to a broad horizon of learning technology and subject matter that has been taught. The ability of students to easily adapt to the use of the internet makes them more creative. The inhibiting factor is the lack of focus of students in following learning due to the distraction of technology and internet web pages. Technology is used in learning only as a learning support so that students do not get bored easily.